METODOLOGIA PARA DETECÇÃO AUTOMÁTICA DE NÓDULOS PULMONARES - Sousa, João Rodrigo Ferreira da Silva (2007)
The lung cancer is a disorder with significant prevalence in several countries worldwide. The hard treatment and the fast progress of the disease increase the mortality rates. The main factor contributing to a successful treatment is an early diagnosis. However possible omissions in the scan analysis can lead to late diagnosis, compromising all the treatment. In order to present a computational tool aimed at nodules detection, that can be used as a second opinion to the specialist, this master thesis proposes a methodology for nodules detection that is totally automatic, robust and consistent. The methodology is based on successive refinements for the segmentation of computed tomography images using morphologic techniques to obtain nodule candidates. The false positive reduction is achieved by SVM based on geometric and texture features. The tests, performed with real scans, indicate the feasibility of the proposed method. In automatic detection performed on 33 cases the methodology reached 95.21% of correctness with 0.42 false positives and 0.15 false negative per scan.